Exploring template-bound dinuclear copper porphyrin nanorings by EPR spectroscopy - Richert, Sabine (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Electron paramagnetic resonance (EPR) spectroscopy has been used to study the molecular geometry as well as metal–ligand interactions in ten-membered porphyrin nanorings (c-P10(Cu2)) containing two copper and eight zinc centers. The presence of copper in the structures allows intramolecular interactions, including dipolar interactions between electron spins and hyperfine interactions to be quantified. Results obtained for c-P10(Cu2) samples bound to two molecular templates with four or five binding sites, respectively, are compared to those obtained for a sample of the porphyrin ring in the absence of any templates. It is shown that the observed lower binding affinity of the nitrogen ligand to copper as compared to zinc has a strong impact on the geometries of the respective template-bound c-P10(Cu2) structures. The interaction between the central copper atom and nitrogen ligands is weak, but pulsed EPR hyperfine techniques such as ENDOR and HYSCORE are very sensitive to this interaction. Upon binding of a nitrogen ligand to copper, the hyperfine couplings of the in-plane nitrogen atoms of the porphyrin core are reduced by about 3 MHz. In addition, the copper hyperfine couplings as well as the g-factors are altered, as detected by continuous wave EPR. DFT calculations of the hyperfine coupling tensors support the assignment of the measured couplings to the nuclei within the structure and reproduce the experimentally observed trends. Finally, Double Electron Electron Resonance (DEER) is used to measure the distances between the copper centers in a range between 2.5 and 5 nm, revealing the preferred geometries of the template-bound nanorings.